Aplikasi Tepung Biji Pepaya sebagai Alternatif Obat Herbal dalam Pengendalian Penyakit Cacingan pada Sapi Potong - Muhammad Surya Atmaja; Dini Widianingrum; Oki Imanudin (Study Program of Animal Husbandry, Faculty of Agricultural, Universitas Majalengka, 2024)
This research aims to analyze the potential of Papaya Seed Flour as an Alternative to Herbal Deworming Medicine in Controlling Worm Disease in Beef Cattle. The research was carried out in Paseh District, Sumedang Regency in January 2024. This research was carried out experimentally. The sampling technique was carried out using purposive random sampling. This research used bulls, aged around 1-1.5 years. This research uses a Pre-test Post-test Control Group Design. The research sample consisted of 10 penned bulls. Before the cow is given treatment in the form of giving the herbal medicine papaya seed flour (Pre-treatment), the cow's feces are taken to be identified and the number of worm eggs infecting the digestive tract is counted. The treatment given is in the form of administering herbal medicine from papaya seed flour (TBP) at a dose of 5g/head, for 3 consecutive days within a period of one week, then testing feces samples (post-treatment) to test the effectiveness of the herbal medicine in reducing levels of and the number of infecting worms. The test parameters in this study were the number of EPGs before and after administration of TBP and FECR until seven days after treatment ended. The research results showed that Papaya Seed Flour has the potential to be an alternative herbal worm medicine in suppressing the growth of digestive tract worms in cattle significantly (p<0.05) with an FECR value reaching 76.9%.